Case Report: Compromised Airway Following Anesthesia and Its Correlation With the Use of ACE Inhibitors—An Unexpected Clinical Event and Review of Literature - Mohanty, Sanjeev; Bangaari, Ashish; Gnanasekaran, Kumaran (Frontiers in Surgery, 2021)
Angiotensin-converting enzyme inhibitors associated angioedema involving the upper aerodigestive tract is indisputably a hazardous airway condition which is clinically poorly recognized and frequently underestimated. We describe and present case of a 70-year old man on ramipril who developed massive tongue swelling post-operatively after unremarkable laryngeal mask anaesthesia which was fortuitously managed conservatively. High index of suspicion, timely recognition and knowledge of pathophysiology and the clinical course should guide airway and further supportive management in these patients.